Molecular pathology of pancreatic cancer. (January 2014) - Saiki, Yuriko; Horii, Akira
<x xml:space="preserve">Abstract</x> By genomic and epigenomic screening techniques, substantial progress has been made in our understanding of pancreatic cancer. The comprehensive studies of the pancreatic cancer genome have revealed that most genetic alterations are identified to be associated with specific core signaling pathways including high‐frequency mutated genes such as KRAS, CDKN2A, TP53, and SMAD4 along with several low‐frequency mutated genes. Three types of histological precursors of pancreatic cancer: pancreatic intraepithelial neoplasia, mucinous cystic neoplasm, and intraductal papillary mucinous neoplasm, had been recognized by morphological studies and the recent genomic screening techniques revealed that each of these precursor lesions were associated with specific molecular alterations. In the familial pancreatic cancer cases, several responsible genes were discovered. Epigenetic changes also play an important role in the progression of pancreatic cancer. Several tumor suppressor genes were silenced due to aberrant promoter CpG island hypermethylation. Several genetically engineered mouse models, based on the Kras mutation, were created, and provided reliable tools to identify the key molecules responsible for the development or progression of pancreatic cancer.